Kinetic and Equilibrium Studies of Adsorption of Cu(II) Ions on Rice Husk† - Sharma, Neeta; Thakur, Anupama; Shivhare, U.S.; Kaur, Manjinder (Asian Journal of Chemistry, 2010)
The present work deals with the removal of copper ions from water by treatment with rice husk. The factors affecting adsorption such as pH, metal ion concentration and time of contact have been varied to obtain an optimum set of conditions for maximum adsorption. It has been observed that maximum adsorption (65%) occurs at pH 10 for a time of contact of 2 h in the concentration range 30–300 mg L–1. The removal is strongly hindered by the presence of a complexing agent such as EDTA. The adsorption data follows the Freundlich and Langmuir isotherm. The results obtained point towards the use of rice husk as a potential adsorbent for copper(II) ions. An attempt to study the kinetics shows that the adsorption of copper ions on rice husk follows first order kinetics as calculated by using the rate equation and confirmed by applying the Lagergren first order rate equation. A tentative mechanism has been proposed.